Developing the Competence of Designing a Collaborative Learning Environment: An Innovative Approach to the Professional Training of Future Teachers - Usmonovna, Kurbonova Gulmira (International Journal on Integrated Education, 2026)
The article highlights the current issues of developing competencies of designing a collaborative learning environment among future teachers in modern education. The study analyzed the impact of interactive and digital technologies on students` skills of effective collaboration in the audience, interpersonal communication and active participation in a team environment. In the article, based on the results of empirical research conducted in pedagogical universities, innovative approaches play a role in increasing the quality of education and the educational motivation of students. Also, ways to further improve the training of future pedagogues through the integration of the digitization process into collaborative education will be shown. The role of these approaches in the future pedagogical practice and promising directions for scientific research are defined.